Automatic Analysis of Operational Failures of Electric Power Station Equipment – Efficient Method for Reduction in Expenditure for Power Generation - V. A. Yanitsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The investigations, executed in the 70-ies-80-ies of the last century, have demonstrated that an operator is badly managing his/her duties and makes mistakes while controlling the operation of power-generating equipment. The developed countries, Russia have developed systems of automatic monitoring for equipment operation which are designed for providing the required data in emergency cases to an operator.A system of automatic detection and analysis of operational failures of electric power station equipment has been developed in the Belarussian Heat Power Engineering Institute and it has been brought into industrial commission.